Partisipasi Politik Pemilih Pemula dan Preferensi Pilihannya dalam Menonton Tayangan Debat Pasangan Calon Presiden dan Wakil Presiden Pada Pemilu Tahun 2024 di Kecamatan Parakansalak Perspektif Siyasah Dusturiyah - Jibril, Muhammad; Sutiana, Yana; Noorisnan Pelita, Bobang (LPPM Universitas Ekasakti Padang, 2024)
Elections are a democratic party because every individual has the right to determine his choice of candidates who he thinks are worthy of being President and Vice President. The debate on presidential and vice presidential candidates is one of the stages in the election, the debate is also a basis for first-time voters to determine their preferences. Siyasah dusturiyah also discusses the criteria for leaders. This research will answer the political participation of novice voters and their preferences in watching debate broadcasts by presidential and vice presidential candidates, which are then reviewed from a siyasah dusturiyah perspective. This type of research is included in the qualitative category using a descriptive analysis method whose data collection technique is through a multistage random sampling method, namely taking samples in stages and then each stage is carried out using a simple random sampling method. The political participation of novice voters in watching presidential and vice presidential debate broadcasts is quite good but not yet optimal due to inadequate socialization and minimal political education. then the preferences of novice voters for their chosen leaders include a clear vision and mission, courage and firmness, being able to act fairly, and broad insight. Of the seven criteria for potential leaders according to Al-Mawardi, six of them are still strong foundations that are very relevant to the preferences of young voters today in order to create state leaders who can bring prosperity to their people.